Analysis Of Endocentric Compound In Greta Thunberg’s Speech School Strike For Climate - Salma Deria Putri; Otong Setiawan Djuharie (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
The formation of new lexical items through the combination of two or more lexemes is referred to as compounding, a significant process within the field of morphology. As noted by O’Grady (1996), compound words are typically categorized into two types: endocentric and exocentric compounds. Katamba (1994:320) emphasizes that endocentric compounds exhibit greater productivity compared to their exocentric counterparts. This study aims to examine the morphological structures of endocentric compound words found in a specific object—namely, the speech text School Strike for Climate. Employing a qualitative-descriptive method, the research analyzes and interprets the semantic classification of the identified compounds. The speech transcript reveals 26 occurrences of endocentric compounds, all of which function as compound nouns and consist of nominal components.